Evaluation of Water Services Public Private Partnership Options for Mid-sized Cities in India - Ehrhardt, David; Gandhi, Riddhima; Mugabi, Josses; Kingdom, William (World Bank, Washington, DC, 2015)
Successful mid-sized cities will be vital to India’s growth and prosperity in the coming decades. Indian cities are home to over 375 million people now, and their population is likely to double by 2035. Yet water supply in most mid-sized cities falls short of Government of India benchmarks for service, efficiency and cost recovery. In many of them water flows in the pipes for 2 hours a day or less, its quality is poor, and it is provided by utilities that cannot even cover their operating costs. Following a brief introduction to the three city case studies (section two), the report lays out the Indian water sector’s unique challenges, and using case examples to substantiate findings (section three). The challenges include day-to-day operational issues associated with running a utility, as well as policy and planning issues that affect the utility’s governance and investment planning to meet current and future demand. The results of a financial viability gap analysis, applied to Bhubaneswar and Coimbatore reveal the magnitude of improvements required, and the key drivers that affect the utilities’ financial performance (section four). These complex challenges make traditional PPP models, Management Contracts, Concessions and Leases, less amenable for use in mid-size Indian cities. As section five describes, this is because the traditional models are too risky for the operator or government or too limited in scope to create lasting improvements. The remaining sections focus on explaining the design and procurement strategy for the two innovative PPP models, the phased performance based contract and the Joint Venture (JV) Partnership (section six and seven). These models have the potential to deliver better results than the traditional PPPs and business as usual scenarios. This is because in addition to reforming dysfunctional utilities into focused and accountable organizations, they are able to respond to information uncertainty, include strong incentives, have clear sources of funding, and promote capital efficiency.